Notatki do Czerniawskiego - Kisiel, Marian (Wydawnictwo Uniwersytetu Rzeszowskiego, 2011)
The article is considered a summa of remarks related to the less known and rarely commented works by an émigré – Adam Czerniawski. The subjects of interpretation are his poems translated into English, miniatures of literary criticism, short novels and his memoirs. Modern Polish prose is still commonly treated as a ciphertext, a subject interesting for but a few readers who revel in this labyrinth of thoughts. It may seem that at the end of our century – a period so involved in discourse with traditional understanding of literature – avant-garde variants of prose should be obvious and legible for everyone or, at least, that literary criticism shall place them on the appropriate level in the hierarchy of modern forms. Apparently, it turned out that the situation is different. The prose model imposed by Positivism still remains predominant in habits and tastes of both literary critics and readers. Few decades of struggle with that one narrative pattern suddenly became questionable. Therefore, the short narrative novels by Czerniawski has not yet been sufficiently analyzed by critics. These narrations are considered – with their Gombrowicz-style grimace – the absolute stories. The feature of absoluteness is visible at all their levels: origin, narration, reading. Everything is possible here but nothing is accidental or random. However, limiting these narrations to only avant-garde rules would with no doubt distort their sense. The prose by Czerniawski uses also infinite potential of grotesque, it plays with its own language and makes out of it an undoubtedly philosophical "Ding an sich". The prose was also written in order to face traditional sanctities such as, for instance, irreformable „Polishness” that glorifies old symbols by perceiving them as hallowed by God’s interference. Finally, the prose by Czerniawski is based on „common sense” that can be found in numerous funny contexts of the surrounding world.
Remarks about Czerniawski
Keywords: Czerniawski Adam; emigracja XX w.; poezja XX w.; proza XX w.